Framing Model of FPI News on MetroTV - Puji Santoso (RIRAI Publisher, 2021)
The research has a specific objective, namely how the national news television station MetroTV media tends to construct news reality about the Islamic Defenders Front Islamic organization which later changed to the Islamic Brotherhood Front or FPI for short in the 2016-2017 period. Furthermore, the content analysis of MetroTV television media will find framing tendencies as well as find framing models on MetroTV television media in constructing news about FPI in the 2016-2017 period. This research method focuses on collecting, analyzing media content (framing studies), and mixing quantitative and qualitative data in a single study or series of studies. The main premise is the use of quantitative and qualitative approaches in combination (mixed method), by providing a better understanding of the research problem because it uses two approaches at once. The main instrument in this study is the researcher himself who collects data through the website from metrotvnews.com in-depth interviews, participatory observations, and conducts relevant documentation studies related to the object under study such as literature, blogspot, internet (online), e-journals, and reports on the results of similar research that are considered relevant. The results of this study found that the news television station under study, namely MetroTV, tends to construct and framing all FPI news that enters the newsroom. In addition, it was found that there is a framing model that MetroTV tends to do. MetroTV's coverage of FPI is always constructed in such a way that it produces text and visuals (frames) which in turn give rise to messages and meanings that give effect and a religious stigma to the masses of Muslims in general.